A Study on the Use of Nonverbal Signals by EFL Students at Tomakaka University During Academic Activities - Fatmawati Fatmawati; Syarifuddin Dollah; Samtidar Samtidar (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2025)
This study analyzes the use of nonverbal signals among English Education students at Tomakaka University, Mamuju, in academic settings. The research aims to describe how students employ nonverbal cues during classroom interactions to demonstrate engagement and facilitate communication. A total of 30 students participated as research subjects. Using a qualitative descriptive design, data were obtained through video recordings, classroom observations, and semi-structured interviews. Content analysis was applied to identify and categorize nonverbal behaviors, with attention to eye contact, gestures, posture, and facial expressions. The results show that students actively used eye contact, hand gestures, posture shifts, and facial expressions as integral components of their communicative practices. These nonverbal behaviors contributed to clearer interaction patterns and supported student participation in the learning process. The study highlights the significance of nonverbal communication in academic contexts and suggests that understanding these cues can assist educators in developing more effective instructional strategies.